Electroencephalogram (EEG) Based Imagined Speech Decoding and Recognition - Sani Saminu; Guizhi Xu; Zhang Shuai; Abd El Kader Isselmou; Adamu Halilu Jabire; Ibrahim Abdullahi Karaye; Isah Salim Ahmad; Abubakar Abdulkarim (AMTS and Faculty of Engineering - Universitas Riau, 2021)
The recent investigations and advances in imagined speech decoding and recognition has tremendously improved the decoding of speech directly from brain activity with the help of several neuroimaging techniques that assist us in exploring the neurological processes of imagined speech. This development leads to assist people with disabilities to benefit from neuroprosthetic devices that improve the life of those suffering from neurological disorders. This paper presents the summary of recent progress in decoding imagined speech using Electroenceplography (EEG) signal, as this neuroimaging method enable us to monitor brain activity with high temporal resolution, it is very portable, low cost, and safer as compared to other methods. Therefore, it is a good candidate in investigating an imagined speech decoding from the human cortex which remains a challenging task. The paper also reviews some recent techniques, challenges, future recommendations and possible solutions to improve prosthetic devices and the development of brain computer interface system (BCI).